Neural respiratory drive, pulmonary mechanics and breathlessness in patients with cystic fibrosis. Issue 3 (1st February 2011) - Reilly, Charles C; Ward, Katie; Jolley, Caroline J; Lunt, Alan C; Steier, Joerg; Elston, Caroline; Polkey, Michael I; Rafferty, Gerrard F; Moxham, John
Abstract : Background: Neural respiratory drive (NRD) measured from the diaphragm electromyogram (EMGdi) reflects the load/capacity balance of the respiratory muscle pump and is a marker of lung disease severity. EMGdi measurement is invasive, but recording the EMG from the parasternal intercostal muscles using surface electrodes (sEMGpara) could provide a non-invasive method of assessing NRD and disease severity. Objectives: To test the hypothesis that NRD measured by sEMGpara correlates with EMGdi, to provide an index of disease severity in cystic fibrosis (CF) and to relate to exercise-induced breathlessness. Methods: 15 patients with CF (mean forced expiratory volume in 1 s (FEV1 ) 53.5% predicted) and 15 age-matched healthy controls were studied. sEMGpara and EMGdi were recorded at rest and during exercise. sEMGpara was recorded using surface electrodes and EMGdi using a multipair oesophageal electrode catheter. Signals were normalised using the peak EMG recorded during maximum respiratory manoeuvres and expressed as EMG%max. The respiratory pattern, metabolic data, oesophageal and gastric pressures and Borg scores were also recorded. Results: Mean (SD) resting sEMGpara%max and EMGdi%max were higher in patients with CF than in controls (13.1 (7)% and 18.5 (7.5)% vs 5.8 (3)% and 7.5 (2)%, respectively, p<0.001). In the patients with CF, resting sEMGpara%max and EMGdi%max were related to the degree of airways obstruction (FEV1 ) (r=−0.91 and r=−0.82, both p<0.001), hyperinflation (r=0.63 and r=0.56, both p<0.001) and dynamic lung compliance (r=−0.53 and r=−0.59, both p<0.001). During exercise, sEMGpara%max and EMGdi%max were strongly correlated with breathlessness in the patients with CF before (r=0.906, p<0.001) and after (r=0.975, p<0.001) the onset of neuromechanical dissociation. Conclusion: sEMGpara%max provides a non-invasive marker of neural drive, which reflects disease severity and exercise-induced breathlessness in CF.